Bitemporal hypoperfusion in transient global amnesia: 99m-Tc-HM-PAO SPECT and neuropsychological findings during and after an attack. Issue 4 (April 1990) - Stillhard, G; Landis, T; Schiess, R; Regard, M; Sialer, G
Abstract : We report a patient who was evaluated neuropsychologically and with single photon emission computed tomography (SPECT) during and after an episode of transient global amnesia. During the attack, there was patchy retrograde amnesia and an inability to learn both verbal and non-verbal material. SPECT showed severe bitemporal hypoperfusion. Serial neuro-psychological testing documented a rapid recovery of recognition, but delayed recovery in reproduction of learned information. Recovery of spontaneous verbal and figural fluency was even further delayed. Follow up SPECT examination showed a recovered cerebral perfusion. This case supports the hypothesis that TGA is associated with transient hypoperfusion of bilateral medial-temporal brain structures and suggests an additional involvement of structures responsible for drive and initiation.